Longitudinal Evolution of Bone Microarchitecture and Bone Strength in Type 2 Diabetic Postmenopausal Women With and Without History of Fragility Fractures—A 5-Year Follow-Up Study Using High Resolution Peripheral Quantitative Computed Tomography - Heilmeier, Ursula; Joseph, Gabby B.; Pasco, Courtney; Dinh, Nhan; Torabi, Soheyla; Darakananda, Karin; Youm, Jiwon; Carballido-Gamio, Julio; Burghardt, Andrew J.; Link, Thomas M.; Kazakia, Galateia J. (Frontiers in Endocrinology, 2021)
Introduction: Diabetic bone disease is characterized by an increased fracture risk which may be partly attributed to deficits in cortical bone quality such as higher cortical porosity. However, the temporal evolution of bone microarchitecture, strength, and particularly of cortical porosity in diabetic bone disease is still unknown. In this study we aimed to prospectively characterize the 5-year changes in bone microarchitecture, strength and cortical porosity in type 2 diabetic (T2D) postmenopausal women with (DMFx) and without history of fragility fractures (DM) and to compare those to nondiabetic fracture free controls (Co) using high resolution peripheral quantitative computed tomography (HR-pQCT). Methods: Thirty-two postmenopausal women underwent baseline HR-pQCT scanning of the ultradistal tibia and radius and a FU-scan 5 years later. Bone microarchitectural parameters, including cortical porosity, and bone strength estimates via µFEA were calculated for each timepoint and annualized. Linear regression models (adjusted for race and change in BMI) were used to compare the annualized percent changes in microarchitectural parameters between groups. Results: At baseline at the tibia, DMFx subjects exhibited the highest porosity of the 3 groups (66.3% greater Ct.Po, 71.9% higher Ct.Po.Volume than DM subjects, p<0.022). Longitudinally, porosity increased significantly over time in all 3 groups and at similar annual rates, while DMFx exhibited the greatest annual decreases in bone strength indices (compared to DM 4.7x and 6.7x greater decreases in failure load (F) and stiffness (K), p<0.025; compared to Co 14.1x and 22.2x greater decreases in F and K, p<0.020). Conclusion: Our data suggest that despite different baseline levels in cortical porosity, T2D women with and without fractures experienced long-term porosity increases at a rate similar to non-diabetics. However, the annual loss in bone strength was greatest in T2D women with a history of a fragility fractures. This suggests a potentially non-linear course of cortical porosity development in T2D bone disease: major porosity may develop early in the course of disease, followed by a smaller steady annual increase in porosity which in turn can still have a detrimental effect on bone strength - depending on the amount of early cortical pre-damage.